Radiative Impacts of Aerosols During COVID-19 Lockdown Period Over the Indian Region - Bhawar, Rohini L.; Fadnavis, Suvarna; Kumar, Vinay; Rahul, P. R. C.; Sinha, Tushar; Lolli, Simone (Frontiers in Environmental Science, 2021)
The COVID-19 lockdown restrictions influenced global atmospheric aerosols. We report aerosol variations over India using multiple remote sensing datasets [Moderate Resolution Imaging Spectroradiometer (MODIS), Ozone Monitoring Instrument (OMI), Cloud-Aerosol Lidar, and Infrared Pathfinder (CALIPSO)], and model reanalysis [Copernicus Atmosphere Monitoring Service (CAMS)] during the lockdown implemented during the COVID-19 pandemic outbreak period from March 25 to April 14, 2020. Our analysis shows that, during this period, MODIS and CALIPSO showed a 30–40% reduction in aerosol optical depth (AOD) over the Indo-Gangetic Plain (IGP) with respect to decadal climatology (2010–2019). The absorbing aerosol index and dust optical depth measurements also showed a notable reduction over the Indian region, highlighting less emission of anthropogenic dust and also a reduced dust transport from West Asia during the lockdown period. On the contrary, central India showed an ∼12% AOD enhancement. CALIPSO measurements revealed that this increase was due to transported biomass burning aerosols. Analysis of MODIS fire data product and CAMS fire fluxes (black carbon, SO2, organic carbon, and nitrates) showed intense fire activity all over India but densely clustered over central India. Thus, we show that the lockdown restrictions implemented at the government level have significantly improved the air quality over northern India but fires offset its effects over central India. The biomass-burning aerosols formed a layer near 2–4 km (AOD 0.08–0.1) that produced heating at 3–4 K/day and a consequent negative radiative forcing at the surface of ∼−65 W/m2 (±40 W/m2) over the central Indian region.